(untitled) (Lafia Journal of Scientific and Industrial Research, 2026)
Geochemistry and mineral potential of Arum and environs, North Central Nigeria, was carried out to evaluate and characterize the major and trace elements composition in the rocks and stream sediments of the area. Sixteen rock samples from four lithologies and eighteen stream sediments were collected at strategic locations. The samples were geochemically analyzed for major and trace elements using X-ray fluorescence. The silica concentrations in the pegmatite and granodiorite range from 76.0 to 79.95 weight percentage (wt%) and 74.09 to 76.01 weight percentage (wt%), respectively, according to the analytical results, which showed that both minerals are extremely siliceous. All of the lithologies in the study area exhibit a slightly consistent concentration of Al2O3, with the ranges being 13.48 to 15.06 in fine to medium grain granite gneiss, 14.65 to 15.91 in medium grain banded gneiss, 13.26 to 14.3 weight percent (wt%) in granodiorite, and 14.26 to 14.65 weight percent (wt%) in pegmatite. The TAS plot of silica saturation index indicates that Arum rocks are granitic, and the aluminum saturation index indicates that Arun rocks are primarily peraluminous. The geochemical concentration shows the spatial distribution and enrichment. The bar-chart concentration plots revealed an uneven anomalous concentration of thorium (Th), tantalite (Ta), niobium (Nb), tin (Sn), and rubidium (Rb) in ppm, compared to their respective background concentration, which revealed a positive anomalous concentration. Arum shows allochthonous mineralization that is structurally controlled and can be regarded as been mineralized in Th, Nb, Sn, U, and Ta.